2010
DOI: 10.1007/s10995-010-0709-1
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Prenatal Group Care Literature: The Need for a Structured Theoretical Framework and Systematic Evaluation

Abstract: The purpose of this article is to systematically review the literature on group-based prenatal care related to patient participation, attendance, satisfaction, knowledge, pregnancy and birth outcomes, and program cost. MEDLINE, CINAHL, and PsycINFO sources were searched for English-language articles published any time prior to June 2010. Manual searches of bibliographies were conducted and experts were consulted to identify possible sources. Descriptive, cross-sectional, cohort, and randomized control studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 15 publications
1
27
0
3
Order By: Relevance
“…As noted in a recent systematic review (35), however, little research exists that explores the mechanisms underlying any beneficial effects associated with group prenatal care. Because our study relied on a retrospective chart review, we did not collect process data on delivery of prenatal care, or extensive antepartum data that might permit empirical examination of the underlying mechanisms behind any observed effects.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in a recent systematic review (35), however, little research exists that explores the mechanisms underlying any beneficial effects associated with group prenatal care. Because our study relied on a retrospective chart review, we did not collect process data on delivery of prenatal care, or extensive antepartum data that might permit empirical examination of the underlying mechanisms behind any observed effects.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Both concluded that women exposed to group prenatal care or CenteringPregnancy yielded significant reductions in PTB, significant improvement in breastfeeding initiation and duration, greater knowledge and satisfaction with prenatal care, and a nonsignificant reduction in cesarean delivery rates and LBW infants. 29,30 Both concluded that women exposed to group prenatal care or CenteringPregnancy yielded significant reductions in PTB, significant improvement in breastfeeding initiation and duration, greater knowledge and satisfaction with prenatal care, and a nonsignificant reduction in cesarean delivery rates and LBW infants.…”
Section: Summary Of Outcomesmentioning
confidence: 99%
“…[10][11][12][13] Group prenatal care and group well-baby care are promising strategies for better addressing family needs and improving clinical and social outcomes. Studies to date have shown that the immediate outcomes associated with group prenatal and well-baby care are at least as good, if not better, than those associated with individual care 11 and in-clude greater satisfaction, [14][15][16] higher breastfeeding initiation rates, [14][15][16] lower rates of preterm birth, [14][15][16] and lower rates of overweight and obesity in children participating in group pediatric care at 15 months 17 and 24 months. 18 However, whether the knowledge and skills gained in group prenatal or group well-baby care are used long term is unknown.…”
Section: Introductionmentioning
confidence: 99%